2012
DOI: 10.1016/j.physb.2011.09.089
|View full text |Cite
|
Sign up to set email alerts
|

Current–voltage temperature characteristics of Au/n-Ge (100) Schottky diodes

Abstract: The variation in electrical characteristics of Au/n-Ge (100) Schottky contacts have been systematically investigated as a function of temperature using current-voltage (I-V ) measurements in the temperature range 140-300 K. The I-V characteristics of the diodes indicate very strong temperature dependence. While the ideality factor n decreases, the zero- . This may be due to greater inhomogeneities at the interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…Both these parameters show inverse correlation with temperature, increasing from 0.51 eV to 1.01 eV and 1.39 to 2.5 at 320 K and 80 K, respectively. The observed increase in the zero-bias barrier height with decreasing temperature is contrary to observations for other semiconductor materials [14,15,9 18, 27, 31, 32]. Results reported in literature for similar studies on the electrical properties of GaSb rectifying structures are conflicting.…”
Section: Current -Voltage Measurementscontrasting
confidence: 58%
See 2 more Smart Citations
“…Both these parameters show inverse correlation with temperature, increasing from 0.51 eV to 1.01 eV and 1.39 to 2.5 at 320 K and 80 K, respectively. The observed increase in the zero-bias barrier height with decreasing temperature is contrary to observations for other semiconductor materials [14,15,9 18, 27, 31, 32]. Results reported in literature for similar studies on the electrical properties of GaSb rectifying structures are conflicting.…”
Section: Current -Voltage Measurementscontrasting
confidence: 58%
“…Although many reports exist on the temperature dependence of current-voltage (I-V) characteristics of metal semiconductor contacts (both ohmic and rectifying) on a number of semiconductors [7,8,9,10,11,12,13,14], to our knowledge, very few such reports exist on GaSb and in particular, epitaxially grown GaSb thin films. Studies have shown that temperature dependent current transport (especially at low temperatures) often cannot be explained satisfactorily by thermionic emission processes alone [7,15,16]. Inconsistency 3 with thermionic emission theory, even for lowly doped (10 15 cm -3 ) material, becomes evident upon plotting the logarithm of the saturation current divided by the square of the temperature against the inverse of the temperature to which a Schottky barrier diode is exposed [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this value is much closer to the theoretical value compared to the value from the conventional Richardson plot. Using the modified Richardson plot in the temperature range of 140~300 K, Chawanda et al obtained the Richardson constant of 1.37 Acm -2 K -2 for the Se/n-Ge Schottky contact [13].…”
Section: Resultsmentioning
confidence: 99%
“…The temperature dependence of current-voltage (I-V) characteristics allows us to understand the different aspects involved in the current transport mechanism. However, most previous studies on Schottky contacts to n-Ge have been limited to the electrical characterization at room temperature and there is little knowledge regarding current transport characteristics in n-Ge Schottky diodes at low temperatures [12,13].…”
Section: Yunae Cho and Dong-wook Kimmentioning
confidence: 99%